1962
DOI: 10.1071/ch9620684
|View full text |Cite
|
Sign up to set email alerts
|

Solvolysis of Sulphonyl Halides. IV. The Hydrolysis of Some Substituted Aliphatic Sulphonyl Chlorides and of Ethanesulphonyl Bromide in Aqueous Dioxan

Abstract: The effects of substitution in the alkyl group of an alkanesulphonyl chloride, on the rate of hydrolysis, vary with the solvent composition. The relative rates can be explained in terms of the theory of Grunwald and Winstein that there is a continuous range of transition complexes, with " bond making " between the water molecule and the sulphur atom controlling the rate in the less aqueous media, u~hile the stretching and charging of the sulphur to chlorine bond controls the rate in solvents of higher water co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1977
1977
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 4 publications
(7 reference statements)
0
2
0
Order By: Relevance
“…When the specific rates of solvolysis of ethanesulfonyl bromide and chloride, in aqueous dioxane at 25.0 °C, are compared as regards their variation with solvent composition [ 19 ], it is found that k Br / k Cl values of modest magnitude fall from 10.9 for a mole fraction of water of 0.205 to a value of 2.8 at a mole fraction of water of 0.990. If the reactions were S N 1 in character with a larger proportion of water in the water/dioxane mixtures, the values would be expected to decrease appreciably because of the stronger solvation by water of a developing chloride ion than of a developing bromide ion [ 24 ].…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…When the specific rates of solvolysis of ethanesulfonyl bromide and chloride, in aqueous dioxane at 25.0 °C, are compared as regards their variation with solvent composition [ 19 ], it is found that k Br / k Cl values of modest magnitude fall from 10.9 for a mole fraction of water of 0.205 to a value of 2.8 at a mole fraction of water of 0.990. If the reactions were S N 1 in character with a larger proportion of water in the water/dioxane mixtures, the values would be expected to decrease appreciably because of the stronger solvation by water of a developing chloride ion than of a developing bromide ion [ 24 ].…”
Section: Reviewmentioning
confidence: 99%
“…Over an eleven-year period (1961)(1962)(1963)(1964)(1965)(1966)(1967)(1968)(1969)(1970)(1971), Hambly and co-workers, published a series of eight papers (Solvolysis of Sulfonyl Halides, Parts I through VIII) [16][17][18][19][20][21][22][23]. In the initial study [16,17] of the solvolysis of the parent benzenesulfonyl chloride and the p-methyl, p-bromo-, and p-nitro derivatives in aqueous dioxane, aqueous acetone, methanol/acetone, and ethanol/acetone, the p-NO 2 (strongest electron-withdrawing influence) was always reacting faster than the parent and the other two derivatives and the overall behavior in a Hammett equation treatment indicated that all were reacting by an S N 2 pathway.…”
Section: Introduction To Solvolyses Of Sulfonyl Halidesmentioning
confidence: 99%